If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 38 = 13x + -18 Reorder the terms: 38 + 6x = 13x + -18 Reorder the terms: 38 + 6x = -18 + 13x Solving 38 + 6x = -18 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 38 + 6x + -13x = -18 + 13x + -13x Combine like terms: 6x + -13x = -7x 38 + -7x = -18 + 13x + -13x Combine like terms: 13x + -13x = 0 38 + -7x = -18 + 0 38 + -7x = -18 Add '-38' to each side of the equation. 38 + -38 + -7x = -18 + -38 Combine like terms: 38 + -38 = 0 0 + -7x = -18 + -38 -7x = -18 + -38 Combine like terms: -18 + -38 = -56 -7x = -56 Divide each side by '-7'. x = 8 Simplifying x = 8
| 9x^2+36x=41 | | -9x^2+36x=-41 | | 6y-3+7=y-5y-16 | | -35=-10x-5 | | 21x^3+3x^2+28x+4=0 | | 7+3x=x-5 | | s=120*3.14*r*10 | | 4x+68=10+14 | | 8r+4=84 | | 28x^3+32x^2+35x+40=0 | | 8w=-21+5w | | y^2+19=12y | | 256x^3+500=0 | | y^2+19-12y=0 | | 5x-3=x-11 | | 15x^3+35x^2+6x+14=0 | | 5x-4=54 | | x(2x+3)=-2 | | 28x^3+32x^2+21x+24=0 | | (x-2)(x+2)+18=12 | | x(3x+4)=-2 | | 8z-2=74 | | 15x^3+126x^2-81x=0 | | 7-6(1-x)=2 | | x-(2x-1)=8-(3x+3) | | A=3.14r^2 | | m-7=-12 | | 3ab+6a+5b+10= | | 14m=18+12 | | X^2+3x-26=0 | | 5x^2+18x-35=0 | | 13y=12(y+19) |